Highly-fluorinated Triaminocyclopropenium Ionic Liquids - Curnow, O.J.; Rathiga, S. (Asian Chemical Editorial Society, 2022)
A series of highly-fluorinated triaminocycloprope nium salts, with up to six fluorous groups, were prepared and their properties as ionic liquids investigated. Reaction of pentachlorocyclopropane or tetrachlorocyclopropene with bis(2,2,2-trifluoroethyl)amine, HN(CH2CF3)2, occurs in the pres ence of a trialkylamine, NR3, to give cations with two fluorinated amino groups, [C3(N(CH2CF3)2)2(NR2)]+ (R=Et, Pr, Bu, Hex), with traces of [C3(N(CH2CF3)2)3] +. Use of appropriate reagent ratios and reaction times and subsequent addition of a dialkylamine, HNR’R”, gives cations with one fluorinated amino group, [C3(N(CH2CF3)2)(NR2)(NR’R”)]+ ((NR2)(NR’R”)= (NBu2)2, (NEt2)(NPr2), (NBu2)(NBuMe)). These cations were isolated as chloride salts and some of these were converted to bistriflamide, dicyanamide and triflate salts to provide ionic liquids. These salts were characterised by thermal (DSC and TGA) measurements and miscibility/solubility properties (determined in a range of solvents). Ionic liquids (ILs) were also characterised by density, viscosity and conductivity measurements where possible. X-ray diffraction studies of chloride salts showed the formation of fluorous regions and more hydrophilic ionic regions in the solid state.